The Conceptual Framework for Problem and Research-Based Learning (PRBL) Model in Learning The Natural Sciences to Empower Students' Analytical Thinking Skills. Issue 1 (March 2021) - Suyatman,; Saputro, Sulistyo; Sunarno, Widha; Sukarmin,
Abstract: Analytical thinking skills are part of critical thinking skills and higher-order thinking skills that are the demands of students in the 21st century. This study aims to produce a conceptual framework for a model in science learning to empower students' analytical thinking skills. The method used in this study was a qualitative method, with the primary source was literature review. Data collection techniques employed literature study which collected data through books and journals. The data obtained from the literature were collected and processed by editing, organizing, and finding the results. Data analysis in this research was content analysis to analyze in-depth the contents of the literature being studied. The results of this study consisted of: 1) The conceptual framework of the modified science learning model is called the problem and research-based learning (PRBL) model, 2) The modified PRBL model has the potential to empower students' analytical thinking skills. This study illustrates to lecturers and subsequent researchers that the modified PRBL model demonstrates the potential to empower analytical thinking skills. The researcher suggests the next researchers conduct research on the application of the PRBL model in the field to test the validity and practicality of the model.